PATTERNS AND INDICA ARCHITECTURE STYLE AS A WEALTH OF CULTURE IN SUPPORTING SPECIAL INTEREST TOUR IN THE CITY OF YOGYAKARTA - INDRO SULISTYANTO (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2017)
Heritage and Cultural Heritage objects loaded with historical and cultural content have a high level of significance to be preserved. This position is reinforced by the resence of a set of legislation that is highly relevant to this need. The parent is the Law of the Republic of Indonesia Number 5 of 1992 on Heritage Objects. Mentioned in the reamble of the Act that the Heritage Preserve is important to be preserved is for the sake of maintaining local identity. For the city of Yogyakarta, it is clear that the Objects of Cultural Heritage and Heritage which became one of the forerunner of ancestral cultures, is a form of identity and a source of pride for the community that should not be eliminated. Heritage and Cultural Heritage objects need to be preserved, not just social cultural life, but also all artifacts, ’petilasan’s and objects that are left with the life of the past. Understanding of Architectural Research and some matters relating to Heritage and Cultural Heritage by architectural style need to be understood. In this research research, limited to Pattern and Style of Architecture in Indie Period which during the past period grow and develop as Heritage and Cultural Heritage objects in Yogyakarta City. Bintaran area becomes a sample of this research activity because of the development of style and pattern of Architecture of Building.